Modeling and Simulation of Mass Recovery Process in Adsorption System for Cooling and Desalination. (May 2017) - Thu, Kyaw; Saha, Bidyut Baran; Mitra, Sourav; Chua, Kian Jon
Abstract: The intrinsic nature of adsorption cycles calls for heat and mass recovery schemes to improve the performance of the system. Energy recovery schemes become highly crucial for adsorption chiller cum desalination plants due to the unavoidable, frequent switching between the heating and cooling phases of the adsorber beds. A comprehensive numerical model for the mass recovery scheme by pressure equalization is developed and the validation with the experimental data is reported. The present model is able to capture the transient pressure response by the adsorbers during the pressure equalization process. It is observed that the specific equalization time exists for optimum mass recovery otherwise the reverse phenomenon occurs tarnishing the positive effect of the mass recovery scheme. Both the experimental and simulation results show that optimum mass recovery time is about 15 to 20 s depending on the heating/cooling temperature sources. The specific daily water production (SDWP) improvement can be as high as 5% by the mass recovery scheme which requires no additional hardware and heat source.